The Determinant of Internet Financial Reporting (IFR): Evidence from Go-Public Companies Listed in IDX - Kharisma Fiendy; Muslim A. Djalil; Jalaluddin Jalaluddin; Nadirsyah Nadirsyah (Proceedings of AICS - Social Sciences, 2018)
The purpose of this study is to see the Internet Financial Reporting (IFR) determinants listed on in Indonesia Stock Exchange (IDX) for the year 2017. The determinants measured by profitability, leverage, Listing and Auditor Reputation as the independent variables. IFR disclosure is measuring by index of Internet financial reporting Index (IFRI) developed by Chen (2000). The population in this research is all go public companies listed on the Indonesia Stock Exchange for the year 2017. By 45 companies that meet the criteria of the research sample has been determined. The data analysis technique are using classical assumption test. Hypothesis testing is using multiple linear regression analysis with SPSS 23.0. The results of this study indicated that all dependent variable (Profitability, Leverage, Listing, and Auditor Reputation) has no significance effect on practice of disclosing Internet financial reporting by reason the nature of IFR and Management Cost.Keywords: Internet financial reporting, level of disclosure, profitability, leverage, listing, auditor reputation.